Relatório de Estágio Profissional - "A aprendizagem no contexto da formação inicial de Professores" - Ana Sofia Tavares Almeida (2018)
This document report has been made aiming the Curricular Unit of the school Placement of the Faculty of Sport of the University of Porto, within the 2nd cycle of Physical Education Teaching on the Primary and Secondary School. Each practicum report has the objective of giving a written account of the pre-service teacher year, according to the lived experiences at school. My school placement has taken place in a school in Vila Nova de Gaia, under the supervision of a Cooperating teacher from the school and a Supervisor from the Faculty of Sport of the University of Porto. This report is divided into five chapters: the first reports my sportive and academic personal experience , the reason to have chosen this path and the personal expectations versus reality/ practice; the second refers to the Setting of Professional Practice, the living experience while Student-trainee within the school context, with all the direct and indirect agents; the third mentions the Professional Practice Performance and is about my experience during the pedagogical practice at school, the set of all my experiences, the organization and management of all this process; the fourth, Professional Development, centres around the research of investigation-action, on the substantive contents of Physical Education classes in the 11th grade class; the fifth is a final sum up of the further perspectives.